Joint implementation and EU accession countries - Mercedes Fernández Armenteros; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2002)
The countries wishing to join the EU have a high potential for low cost greenhouse gas emission reduction. As they cannot join the ?bubble? agreement for the first commitment period of the Kyoto Protocol, project-based Joint Implementation (JI) could be a powerful strategy to integrate accession countries into an overall EU climate policy strategy. An important question in this context is whether the ?acquis communautaire? will be used to define the baseline for the calculation of emission reductions from JI projects. A problem is that the grace periods for several environmental sectors, e.g. for application of the IPPC directive, differ considerably among countries. The EU should help accession countries to establish a predictable legal framework on which to base JI preventing in this way the current legal uncertainty regarding procedures of JI. Moreover, it should aim at an early implementation of the monitoring guideline and couple it with technical assistance. This would allow to build strong inventory systems in the accession countries and thus avoid the risk that JI is restricted to the second, strongly supervised track. – – In den Ländern, die der EU in den nächsten Jahren beitreten wollen, gibt es ein erhebliches Potenzial kostengünstiger Maßnahmen zur Treibhausgasverringerung. Da die Beitrittsländer der EU-Zielgemeinschaft für die 1. Verpflichtungsperiode des Kyoto- Protokolls nicht beitreten können, könnte projektbasierte Joint Implementation (JI) eine wichtige Strategie zur Integration dieser Länder in eine EU-weite Klimapolitikstrategie sein. Eine wichtige Frage ist in diesem Zusammenhang, ob der ?Acquis Communautaire? die Referenzfälle für die Berechnung der Emissionsverringerung aus JI-Projekten bestimmt. Problematisch hierbei ist, dass sich die Übergangsperioden für verschiedene Sektoren, z.B. für die Anwendung der IVU-Richtlinie, zwischen den Ländern erheblich unterscheiden. Die EU sollte den Ländern bei dem Aufbau eines Rechtsrahmens für JI unterstützen, um die derzeitige rechtliche Ungewissheit zu beseitigen. Außerdem sollte sie eine frühzeitige Umsetzung der Berichterstattungs- Richtlinie anstreben und dies mit technischer Hilfe verknüpfen. Somit könnten gute Inventarsysteme aufgebaut werden und ausgeschlossen werden, dass JI auf den zweiten, kontrollintensiven Weg eingeschränkt wird.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Internationaler Transfer; EU-Erweiterung; EU-Staaten; Osteuropa; joint implementation